FROM THE SITE TO THE LOGIC OF A PLACE: rehabilitation of three residential buildings in Porto (competition, 1st prize) - Pinto, P.; Miranda, Bernardo Pizarro (Design Research (in) Practice II, 2018)
This presentation will show how in the design submitted to a contest the work method would be decisive for the condition of the overall final solution. In this methodology drawing remains as a research instrument, but it is either associated and putted at the service of a more complex mechanism: a critical thinking about the circumstances and cultural significance of the design problem. The team brings together two architectural design teachers and, in a way, reflects in its operating methodology a process where formal values are framed and evaluated in the context of a collaborative process: as a team work, hence constituting a synthesis that represents multiple circumstances, on which architecture “depends” and which does not necessarily transcend. The design of decisions was built upon a process, which includes validation tools such as diagrams and analytical schemes, in addition to the traditional argumentation in work meetings. In these design case the circumstances were varied and included urbanistic, architectural, historical, economic, technological, cultural and artistic aspects. Some of the aspects will be markedly social and collective, others seemingly more individual. Overall, the solution is a synthesis that runs several risks, both positive and negative, including, in this case, a proposed “programmatic and functional shock", that will provide a new intensity and identity to the competition place